Clinical characteristics of single human papillomavirus 53 infection: a retrospective study of 419 cases - Ruizhe Chen (BMC, 2021)
Abstract Background Human papillomavirus (HPV) infection is the main cause of cervical cancer. Characteristics of HPV infections, including the HPV genotype and duration of infection, determine a patient’s risk of high-grade lesions. Risk quantification of cervical lesions caused by different HPV genotypes is an important component of evaluation of cervical lesion. Data and evidence are necessary to gain a deeper understanding of the pathogenicity of different HPV genotypes. The present study investigated the clinical characteristics of patients infected with single human papillomavirus (HPV) 53. Methods This retrospective study analyzed the clinical data of patients who underwent cervical colposcopy guided biopsy between October 2015 and January 2021. The clinical outcomes and the follow-up results of the patients with single HPV53 infection were described. Results 82.3% of the initial histological results of all 419 patients with single HPV53 infection showed negative (Neg). The number of patients with cervical intraepithelial neoplasia (CIN)1, CIN2, CIN3, vaginal intraepithelial neoplasia (VaIN)1, CIN1 + VaIN1, CIN1 + VaIN2, and CIN2 + VaIN2 was 45, 10, 2, 9, 6, 1, and 1, respectively. Cancer was not detected in any patient. When the cytology was negative for intraepithelial lesion or malignancy (NILM), atypical squamous cells of undetermined significance (ASC-US) or low-grade squamous intraepithelial lesion (LSIL), we observed a significant difference in the distribution of histological results (P < 0.05). 95 patients underwent follow-up with cytology according to the exclusion criteria. No progression of high-grade lesions was observed during the follow-up period of 3–34 months. Conclusions The lesion caused by HPV53 infection progressed slowly. The pathogenicity of a single HPV53 infection was low.